Students' sense of belonging and its impact on effectively teaching about environmental changes in high latitudes during a master's programme - Särkelä, Karoliina; Salovaara, Janne J.; Vesterinen, Veli-Matti; Siponen, Joula; Salmela-Aro, Katariina; Riuttanen, Laura; Lauri, Katja Anniina (Copernicus, 2026)
Sense of belonging plays a significant role in students' academic success. For the “Environmental Changes at Higher Latitudes” master's programme, success is effectively communicating geoscience research and ideas to the students. This study explores students' perceived sense of belonging, the conditions for belonging among master's students of this particular programme, and the impact of belonging on educational effectiveness in a climate change context. This programme is organised jointly between universities of three Nordic nations and for it – and for the multilocality of the geoscience themes – has a particularly high degree of mobility. Therefore, the programme lacks elements present in a typical higher education experience, such as on-site attendance in a physically shared space with a relatively stable group of peers and instructors which are thought significant for the students' feelings of belongingness. Based on 15 interviews, we elaborate on the findings of the students' motivation, ability and opportunities to belong and on the construct of their perceived belonging. Emerging from this study, these constructs for sense of belonging consist of the students' sense of familiarity – familiar elements in the place, surroundings and culture; sense of recognition – recognised by oneself and others as a peer and a member of the knowledge community; and last, sense of relevance – finding their studies relevant and interesting. Due to the unique set-up of the programme, the study reveals insight into elements that support the sense of belonging, crucial especially in such geoscience and climate education and communication that might lack the typical shared physical space of a programme, but applicable to curriculum design and development of any programme with high degree of mobility.